Güncel bir cam iyonomer restoratif sistemin 36-aylık klinik performansının değerlendirilmesi - Esra Ergin; Filiz Yalçın Çakır; Sema Öztaş; Sevil Gürgan; Zeynep Kütük (Cumhuriyet University, 2014)
Objectives: To evaluate the 36 month clinical performance of a current glass-ionomer restorative system by comparing with a micro-filled resin composite, on Class II cavities.Materials and Methods: Sixty cavities in 26 patients were randomly divided into two groups according to the restorative systems used (n=30); the cavities in Group 1 were restored with a glass-ionomer restorative system (EQUIA/GC); packable glass-ionomer (Fuji IX GP EXTRA/GC)+self-adhesive nano-filled coating (G-Coat PLUS/GC); whereas the ones in Group 2 were restored with a micro-filled composite (Gradia Direct/GC)+a self-etch adhesive (G-Bond/GC). The restorations were evaluated at  1 week (baseline), 6, 12, 18, 24 and 36 months according to the modified USPHS criteria. The data were statistically evaluated by Pearson Chi-Square test (p=0. 05).Results: Fifty-three restorations were evaluated in 23 patients after 36 months.  All the restorations in the two groups were scored as Alpha for recurrent caries, surface texture, postoperative sensitivity and color match. For marginal adaptation, 6 restorations (23.7%) in Group 1 and 8 restorations (29.6%) in Group 2 were scored as Bravo. Two restorations ( 7.6%) in Group 1 and 5 restorations (18.5%) in Group 2 were scored as Bravo for marginal discoloration. One restoration (3.8%) in Group 1 was scored as Charlie for anatomic form and retention because of marginal fracture within restorative material.  However, there were no significant differences between the clinical performances of the materials (p>0. 05).Conclusions: Both materials exhibited a similar and clinically acceptable performance on moderate Class II cavities after 36-months. ÖZETAmaç: Bu çalışmada, güncel bir cam-iyonomer restoratif sistemin II. sınıf kavitelerdeki 36-aylık klinik performansını, mikro-dolduruculu bir kompozit rezinle kıyaslayarak değerlendirilmek amaçlanmıştır.     Gereç ve Yöntem: Yirmi altı hastadaki toplam 60 II. sınıf kavite, kullanılan restoratif sisteme göre rastgele iki gruba ayrılmıştır (n=30). Grup 1'deki kavitelere cam iyonomer restoratif sistem (EQUIA/GC); kondanse edilebilir cam-iyonomer Fuji IX GP EXTRA+self-adeziv nano-dolduruculu yüzey örtücü G-Coat PLUS; Grup 2'deki kavitelere ise, mikro-dolduruculu kompozit rezin (Gradia Direct/GC)+self-etch adeziv (G-Bond/GC) uygulanmıştır. Restorasyonlar uygulandıktan 1 hafta sonra (başlangıçta)  ve 6.,12.,18., 24. Ve 36. aylarda modifiye USPHS kriterlerine göre değerlendirilmiş, elde edilen veriler Pearson Ki-kare testi ile istatistiksel olarak analiz edilmiştir (p=0. 05).     Bulgular: 36. ayda, 23 hastada 53 restorasyon değerlendirilmiştir. Retansiyon, anatomik form, sekonder çürük, yüzey yapısı, post-operatif duyarlılık ve renk uyumu yönünden her iki grupta tüm restorasyonlar Alfa olarak skorlanmıştır. Grup 1'de 6 (%23.7), Grup 2'de 8 (%26.6)restorasyonun kenar uyumu; Grup1'de 2 (%7.6), Grup 2'de ise 5(%18.5) restorasyonun kenar renklenmesi Bravo olarak skorlanmıştır. Grup1'de 1 restorasyonda kenar kırığı gözlenmiş,anatomik form ve retensiyon yönünden Çarli olarak skorlanmıştır.  Ancak, materyallerin klinik performasları arasında  istatistiksel olarak anlamlı fark yoktur(p>0. 05).     Sonuçlar: 36 ay sonunda, II. Sınıf kavitelerin restorasyonunda her iki materyal benzer ve kabul edilir klinik performans göstermiştir.